METAPHORS USED IN BOB DYLAN’S SONGS - Muh. Ma'rifatullah; Murni Mahmud; Abd. Halim (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
This study aims to determine the types of metaphors, and the functions of metaphors contained in Bob Dylan's songs. This research is descriptive qualitative research because the purpose of this research is to describe phenomena that occur in terms of language. The data source for this research is Bob Dylan's songs, namely "Blowing in The Wind" and "The Times They Are A-Changing". In analyzing the data, the researcher used theories from Leech (1984) and J.J.A Mooij (1993). In this study, researcher obtained four types of metaphors. The types of divided metaphors are concretive metaphor, animistic metaphor, humanizing metaphor, and synesthetic metaphor. As for the study of metaphorical functions, there are three functions, namely the emotive function, the persuasive function, and the cognitive function. Keywords— Metaphor, Types of Metaphor, Functions of Metaphor, Bob Dylan